Treatment with bisphosphonates to mitigate calcification of elastin‐containing bioprosthetic materials. Issue 7 (9th April 2020) - Zhuravleva, Irina Y.; Polienko, Yuliya F.; Karpova, Elena V.; Timchenko, Tatyana P.; Vasilieva, Maria B.; Baratova, Ludmila A.; Shatskaya, Svetlana S.; Kuznetsova, Elena V.; Nichay, Nataliya R.; Beshchasna, Natalia; Bogachev‐Prokophiev, Alexander V.
Abstract: This study evaluated the ability of bisphosphonates (BPAs) of different molecular structures to mitigate the calcification of porcine aortic wall (PAW) and bovine jugular vein wall (BJVW). Tissues cross‐linked with glutaraldehyde (GA) or diepoxide (DE) were modified with pamidronic acid (PAM), alendronic acid (ALE), neridronic acid (NER) (type 1 BPAs); 2‐(2′‐carboxyethylamino)ethylidene‐1, 1‐bisphosphonic acid (CEABA), 2‐(5‐carboxypentylamino)ethylidene‐1, 1‐bisphosphonic acid (CPABA) (type 2); and zoledronic acid (ZOL) (type 3). After implanting the tissue samples subcutaneously in 100 rats, calcification was examined using atomic absorption spectrophotometry (60‐day explants) and light microscopy after von Kossa staining (10‐ and 30‐day explants). The calcium contents in GA‐BJVW and GA‐ and DE‐PAW increased up to 100–120 mg/g after 60 days, while being 3 times lower in DE‐BJVW. In modified and nonmodified PAW samples, calcium phosphates appeared by day 10 and were associated with elastic fibers and devitalized cellular elements. In all groups of BJVW samples, mineralization began in elastic fibers near the subendothelial layer. In addition, calcified collagen was found in the GA‐BJVW samples. Minimal calcification was found in GA‐PAW treated with type 1 BPAs and CEABA. For DE‐PAW and GA‐BJVW, the calcium level significantly decreased with PAM and CEABA. Meanwhile, ALE and NER were effective for DE‐BJVW.